LONG JUMP IN ASIAN GAMES: CONTEXT OF PISA-LIKE MATHEMATICS PROBLEMS - Ika Pratiwi; Ratu Ilma Indra Putri; Zulkardi Zulkardi (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2019)
This study aimed to produce a set of PISA-like mathematics problems content of uncertainty and data using long jump context in Asian Games that were valid, practical and had potential effects on the ability of the students’ mathematical literacy. This study used the design research method of development studies type in two stages, preliminary and formative evaluation. The subject of this study involved 34 students of Senior High School. The result of this study was a set of PISA-like mathematics problems using long jump context in Asian Games which were valid, practical, and had potential effects. The result of students’ answer analysis showed some strategies and arguments used by students. In question 1, 3 out of 34 students were involved in representation, reasoning and argument ability, 31 out of 34 students were involved in reasoning and argument ability. In question 2, 30 out of 34 students were involved in representation and reasoning and argument ability, and 4 out of 34 students were involved in communication, representation, reasoning and argument ability. Also, using the PISA-like mathematics problems with long jump context made students more interested and active during the learning process.